Human Resource Development Strategy For Women MSMEs Based On Local Wisdom On The Surabaya Coastal - Nofandi, Faris; Kusumawati, Elly; Annas Amrullah, Romanda; Mochklas, Mochammad; Sa’diyah, Halimatus (UMSurabaya Publishing, 2024)
Women are human resources with potential that can be utilized in various fields. Women's MSMEs can potentially improve coastal communities' welfare, independence, and empowerment. To overcome these challenges and obstacles, women's MSME businesses on the coast of Surabaya must develop several strategies for human resources for MSME actors on the coast. The research method in this study was quantitative; questionnaires were distributed to female MSME actors on the coast of Surabaya in Tambak Wedi, Kedinding, Nambangan, Bulak, Kenjeran, and Wonorejo. Eighty-two female MSME actors have filled out the questionnaire appropriately, and the data entered is processed and analyzed using SEM PLS. This research shows that the training variable has a significant positive effect on the development of human resources for female MSMEs on the coast of Surabaya. Meanwhile, other variables, such as education, health, motivation, and involvement, do not influence the development of human resources for female MSME actors on the coast of Surabaya